Robot Manipulation Trajectory Planning in Complex Position - Samin, Razali (2002)
The study proposed and demonstrated a strategy smooth trajectory planning to follow the path constrained with time optimal trajectories for the manipulator. The problem in trajectory planning was to find a smooth trajectory function and optimal joint optimisation processes. Such trajectories were obtained by considering the kinematics properties for velocities, accelerations and jerks profiles in joint coordinates for the end-effector to move the path constraints. The method was based on the position profile composed of three polynomial segments such as 4-3-4, 3-5-3 and 3-cubic trajectory and five polynomial segments for 5-cubic trajectory. These polynomial segments combination allowed the analytical solution to the minimum time trajectory problem under consideration of velocity, acceleration and jerk by using Mathematica software. A number of simulations were performed to demonstrate the trajectory methods using robot simulation PUMA 560 model. The robot simulation model was developed using Mechanical Desktop software and the analytical analysis was done using visualNastran software. The simulations showed that the trajectory ability methods for the investigation under varying time ratio conditions and the operations such as Pick and Place Operation (PPO) and Continuous Path (CP). For comparison on varying time ratio 4-3-4 gave a reasonably smooth for normal trajectory condition and a ramp at middle segment to generate a minimum free-space time compared to 3-5-3 and cubic trajectories. For PPO and CP, 4-3-4 trajectory generated a lower values for accelerations and jerks compared to 3-5-3 and cubic trajectories. This showed the 4-3-4 trajectory was the best type of joint interpolated trajectory planning for any path planning operations.